2015
DOI: 10.1007/s11606-015-3228-3
|View full text |Cite
|
Sign up to set email alerts
|

Internal Medicine Residents’ Perceptions of Team-Based Care and its Educational Value in the Continuity Clinic: A Qualitative Study

Abstract: BACKGROUND :In order to teach residents how to work in interprofessional teams, educators in graduate medical education are implementing team-based care models in resident continuity clinics. However, little is known about the impact of interprofessional teams on residents' education in the ambulatory setting. OBJECTIVE: To identify factors affecting residents' experience of team-based care within continuity clinics and the impact of these teams on residents' education. DESIGN: This was a qualitative study of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
12
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 23 publications
1
12
0
Order By: Relevance
“…Direct workplace observation of a resident giving feedback to an interprofessional colleague may not be feasible and simply placing learners in team-based care may be insufficient to teach these skills. 23,24 Performance-based assessment such as OSCEs may be an ideal, efficient strategy for providing program needs assessments and educational opportunities in these critical but difficult to directly observe milestones.…”
Section: Discussionmentioning
confidence: 99%
“…Direct workplace observation of a resident giving feedback to an interprofessional colleague may not be feasible and simply placing learners in team-based care may be insufficient to teach these skills. 23,24 Performance-based assessment such as OSCEs may be an ideal, efficient strategy for providing program needs assessments and educational opportunities in these critical but difficult to directly observe milestones.…”
Section: Discussionmentioning
confidence: 99%
“…Given the importance of role clarity with regard to IPC [ 3 , 4 ], we sought to delve deeper into this issue by analyzing whether or not various components of residents’ and nurses’ roles were translated into action. Role components for which participants’ actions matched their perceptions may be understood as favoring collaborative practice.…”
Section: Discussionmentioning
confidence: 99%
“…Analyzing how healthcare teams work together, Grumbach and Bodenheimer [ 3 ] observed that having common and well-defined goals, institutional stability, being trained to perform one’s role, communication, and role clarity were essential elements of IPC. Professional role therefore represents an important aspect of IPC [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Soones et al provide some insight into interprofessional collaborative care through a qualitative study that explores the factors internal medicine residents identified as affecting their ability to provide and learn about interprofessional team-based care, with a focus on residents' continuity clinics. 8 Although residents believed teams could improve patient care and healthcare provider job satisfaction, the opportunities to experience this and learn from these experiences were hindered by the system within which they worked. Specific challenges included absences created by residents' schedules, frequent team member turnover, low staffing ratios, and a negative cultural perception that residents will do all of the work when teams break down.…”
mentioning
confidence: 99%